The Impact of The Minimum Age Limit Regulation for Continuing Child Marriage After the Birth of Law Number 16 Of 2019 on The Child's Future - Hayati, Amal; Hudafi, Hamsah; Mardiana, Juli; Limbong, Abdul Kalam (El-Usrah: Jurnal Hukum Keluarga, 2023)
Regulations will always be present as a compass so that humans as social creatures do not run away from the right path. This study shows from a direct perspective from society's perspective the impact of the Minimum Age Regulations for Entering into Child Marriages After the Birth of Law Number 16 of 2019 on the future of children which is studied by looking at how much the implementation of this law is in line with the current rules and habits of society. By using a descriptive research method, the author aims to be able to obtain results from research carried out using a Sociological Juridical approach, namely assessing the work of law in society because the functioning of law in society can be seen from the level of legal effectiveness. From the results of research on the impact of regulations on the minimum age limit for entering into a child marriage after the birth of Law Number 16 of 2019 on the future of children, it is clear that the law or a rule must always be updated so that it cannot be broken by developments in society's behavior as a legal subject